Operating modes and cost burdens for the European deposit-refund systems: A systematic approach for their analysis and design. (15th March 2021) - Calabrese, A.; Costa, R.; Levialdi Ghiron, N.; Menichini, T.; Miscoli, V.; Tiburzi, L.
Abstract: Deposit-Refund Systems (DRS) are one of the most effective methods to collect one-way beverage packaging. Yet, the analysis of their operating modes and related cost burdens for each actor are still evolving. This study analyses the operating modes and the cost burdens of ten European DRS' using a number of building blocks shared among the different systems. This approach facilitates their comparison and the development of new models. The building blocks are identified through content analysing some relevant reports. The results show that the required building blocks are the four actors in the process – namely the DRS operator, producers, retailers, and customers –, the money-material flows among the actors (operating mode), and the costs and revenues for each actor (cost burden). Using this approach, the ten models in Europe are reduced to four DRS archetypes. Each archetype has a different money-material flow and a different cost burden for each actor. There are in total 18 costs and 9 revenues. This study contributes to the systematic analysis of DRS′ in terms of their operating modes and related cost burdens for each actor. Using building blocks to describe the DRS′ facilitates the comparison of different models and the analysis of their efficiency and effectiveness. Moreover, it provides a tool to develop new, country-specific DRS′ in those areas where DRS' do not exist. Highlights: Deposit-Refund Systems (DRS) apply a price surcharge on polluting products refunding it when the product is returned. One of their primary goals is the recycling of one-way beverage packaging. There are different DRS models in Europe that can be analysed by using a number of building blocks. By analysing European DRS models through such building blocks, four DRS archetypes have been identified. This analysis facilitates the comparison of different DRS models and the development of new ones.